2011
DOI: 10.1002/pat.2073
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high thermal conductive aluminum nitride/cyanate ester nanocomposite using a new macromolecular coupling agent

Abstract: Novel glycidyl methacrylate–butyl acrylate–maleic anhydride (GBM) terpolymers with different molecular weights were synthesized by radical polymerization and characterized using fourier transform infrared, nuclear magnetic resonance (1H‐NMR and 13 C‐NMR), and gel permeation chromatography. Each GBM terpolymer was used to modify aluminum nitride (AlN), and the modified AlN, coded as AlN(GBM), was added to 2,2′‐bis(4‐cyanatophenyl)isopropylidene (CE) resin for preparing composites. Composites based on original A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The adhesion at the interface between the polymer matrix and the fillers is essential to the thermal conductivity of composites. Many studies showed that the surface treatment with coupling agent can improve the matrix-filler interfacial adhesion, which increases the thermal conductivity of composites [141][142][143]. Thermal boundary resistance (R b ) is a measure of an interface's resistance to thermal flow.…”
Section: Thermally Conductive Polymer Compositesmentioning
confidence: 99%
“…The adhesion at the interface between the polymer matrix and the fillers is essential to the thermal conductivity of composites. Many studies showed that the surface treatment with coupling agent can improve the matrix-filler interfacial adhesion, which increases the thermal conductivity of composites [141][142][143]. Thermal boundary resistance (R b ) is a measure of an interface's resistance to thermal flow.…”
Section: Thermally Conductive Polymer Compositesmentioning
confidence: 99%
“…To further improve the thermal conductivities of the epoxy polymers, one simple method is to introduce ceramic particles with high thermal conductivity into the matrix. A variety of fillers including alumina (Al 2 O 3 ), [2] aluminum nitride (AlN), [3][4][5] and boron nitride (BN) [6] are chosen for the preparation of high thermal conductivity polymer composites. Among these fillers, AlN nanoparticles have received great attention because of their good physical properties, such as abrasion resistance, corrosion resistance, thermal stability, electrical insulation, and high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [12] prepared a novel substituted biphenyl-based cyanate ester resin (Figure 11.13). The monomer, 4,4 0 -bis(4-cyanatobenzyl)biphenyl (BBPCy) does not contain any phosphorous or halogen atoms and hence, avoids the drawbacks involved with such compounds like, for instance, the generation of toxic fumes upon thermal combustion of halogen-containing compounds.…”
Section: Monomers Conferring Flame Retardancementioning
confidence: 99%
“…12 Chemical structures of the DOPO modified cyanester monomers used by Chang et al[92] (structures a and b) and Lin et al[91] (structure c).OCN NCOFigure 11.13 Chemical structure of 4,4 0 -bis (4-cyanatobenzyl) biphenyl (BBPCy)[12].…”
mentioning
confidence: 99%